Preservice Teachers’ Perception Levels Concerning Consumer Environmental Consciousness - Yurdal Dikmenli (Journal of Education in Science, Environment and Health)
People who strive to prevent harm to the environment while utilizing it and to maintain a livable environment is related to educational and cultural values. If we want the next generation to live in an environment as undisturbed as we live in now, environmentally friendly products should be consumed and waste should be prevented. Thus, raising an environmental consciousness among consumers is of vital importance. Environmental consciousness is shaped by individuals’ knowledge, attitudes, sensitivity and beneficial behavior towards environment. In this sense, the primary aim of this study is to determine preservice teachers’ perception levels of consumer environmental consciousness in terms of different variables. The sample of the study consists of 396 preservice teachers from various departments in the Faculty of Education in Ahi Evran University between the 2015-2016 academic years. 70.2% of the sample is female while 29.8% is male. The Consumer Environment Consciousness Scale (CESS) which was developed by the researcher, and contains 28 items, 20 of which are positive and 8 of which are negative, was used for data collection. The gathered data was analyzed using SPSS 17 software. The study findings suggest that the participant preservice teachers have a medium level of consumer environment consciousness and this consciousness differs significantly in terms of gender, income level and whether or not they have had environment lessons before. Additionally, there was found to be no meaningful difference in perception levels in terms of residential area the participants live in.